2012
DOI: 10.1088/1367-2630/14/11/113031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental phase diagram for random laser spectra

Abstract: We systematically study the presence of narrow spectral features in a wide variety of random laser samples. Less gain or stronger scattering are shown to lead to a crossover from spiky to smooth spectra. A decomposition of random laser spectra into a set of Lorentzians provides unprecedented detail in the analysis of random laser spectra. We suggest an interpretation in terms of mode competition that enables an understanding of the observed experimental trends. In this interpretation, smooth random laser spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Hence, the theoretical approach also includes the fact that RLs are open dissipative systems with an external pumping mechanism and radiation losses [8]. In our experiments the disorder is fixed and the nonlinearity increases with the pumping energy, which acts as the inverse of temperature in statistical mechanics [26,27]: at low energy (high temperature) there is no gain competition [28,29] between the modes and they oscillate independently in a continuous wave paramagnetic regime; while at high energy (low temperature) the coexistence of mode coupling through the gain competition and frustration due to disorder gives rise to a glassy regime. In this regime a large number of electromagnetic modes is activated and in interaction.…”
Section: Spin-glass Theory Of Random Lasersmentioning
confidence: 99%
“…Hence, the theoretical approach also includes the fact that RLs are open dissipative systems with an external pumping mechanism and radiation losses [8]. In our experiments the disorder is fixed and the nonlinearity increases with the pumping energy, which acts as the inverse of temperature in statistical mechanics [26,27]: at low energy (high temperature) there is no gain competition [28,29] between the modes and they oscillate independently in a continuous wave paramagnetic regime; while at high energy (low temperature) the coexistence of mode coupling through the gain competition and frustration due to disorder gives rise to a glassy regime. In this regime a large number of electromagnetic modes is activated and in interaction.…”
Section: Spin-glass Theory Of Random Lasersmentioning
confidence: 99%
“…The coherent feedback due to randomly self-generated cavities among different displacements of scatterers and also Anderson localization has been proposed for strongly scattering media1617. Another scenario has been theorized in weakly scattering systems, with extended modes that interact among them via the competition for the available gain18. In this picture, the origin of random peaks has a statistical meaning, with an incoherent non-resonant feedback that leads to a prevalence and to an exceptional growing of few long-lived modes among the others1920.…”
mentioning
confidence: 99%
“…To describe the scattering strength provided by the cells, the scattering mean free path s is defined as the average distance that light travels between two consecutive scattering events. This parameter is determined as 33,34 Figure 4b. Moreover, it has been reported that the refractive index of the normal cells is lower than that of the cancerous cells.…”
Section: Lasing Mechanism Of the Bfrl Filled With The Cellsmentioning
confidence: 99%